Signifikansi Eksorsisme bagi Pelayanan Yesus menurut Ketiga Injil Sinoptik dan Implementasinya dalam Konteks Indonesia - Carel Hot Asi Siburian (CARAKA: Jurnal Teologi Biblika dan Praktika, 2023)
This article will discuss the theme of Jesus as an exorcist and its significance to His ministry from the perspective of the Synoptic Gospels. The conclusions of this article are: 1) Jesus’ ministry of exorcism is unique because Jesus casts out demons on His own authority and shows the realization of God’s salvation for mankind, 2) the ministry of exorcism must remain an integral part, task, and calling of the church in the world until the end of time, 3) that a person who does not even know Jesus can cast out demons in the name of Jesus (Mark 9:38-41; Luke 9:49-50), where it shows that the name of Jesus has power over demons, and finally, and finally, 4) the implementation of the story of Jesus as an exorcist for the Indonesian context, that the church must be able to restore the existence of exorcism in the midst of cultural diversity, and perhaps even make efforts to contextualize it with culture in terms of exorcism in the name of Jesus. The method used is a literature study on the stories of exorcism by Jesus according to the Synoptic Gospels. This article will conclude that exorcism by Jesus will always be centered on the presence of the Kingdom of God in the world and in the future.